Mastering Skype for business 2015 - Hanna, Keith (John Wiley and Sons, 2016)
Authoritative, hands-on guidance for Skype Business administrators Mastering Skype for Business 2015 gives administrators the comprehensive coverage they need to effectively utilize Skype for Business. Fully up to date for the 2015 release, this guide walks you through industry best practices for planning, design, configuration, deployment, and management with clear instruction and plenty of hands-on exercises. Case studies illustrate the real-world benefits of Unified Communication, and provide expert experiences working with Skype for Business. From server roles, infrastructure, topology, and security to telephony, cloud deployment, and troubleshooting, this guide provides the answers you need and the insight that will make your job easier. Sample automation scripts help streamline your workflow, and full, detailed coverage helps you exploit every capability Skype for Business has to offer. Skype for Business enables more robust video conferencing, and integrates with Office, Exchange, and SharePoint for better on-premises and cloud operations. Organizations are turning to Skype for Business as a viable PBX replacement, and admins need to be up to speed and ready to go. This book provides the clear, explicit instructions you need to: -Design, configure, and manage IM, voice mail, PBX, and VoIP -Connect to Exchange and deploy Skype for Business in the cloud -Manage UC clients and devices, remote access, federation, and public IM -Automate management tasks, and implement cross-team backup-and-restore The 2015 version is the first Skype to take advantage of the Windows 10 'touch first' capabilities to provide fast, natural, hands-on control of communications, and users are eager to run VoIP, HD video conferencing, collaboration, instant messaging, and other UC features on their mobile devices. Mastering Skype for Business 2015 helps you get Skype for Business up and running quickly, with hands-on guidance and expert insight.